Recent progress in stretchable organic field-effect transistors: key materials, fabrication and applications. (27th February 2023) - Weng, Yun; Yu, Zhaohui; Wu, Ti; Liang, Lijuan; Liu, Shengzhen
Abstract : We summarize the recent progress in the application of high-performance STOFETs achieved by developing stretchable channel materials and processing techniques. Abstract : Stretchable electronic devices as an emerging electronic application product break the limitations of traditional planar rigid circuits and further expand the application fields of optoelectronics. Stretchable organic field-effect transistors (STOFETs) are an indispensable class of stretchable electronic devices, especially in wearable electronics, implantable electronics and skin like electronics. Therefore, extensive research effort has been devoted to the development of high-performance STOFETs, and remarkable advances in materials, processing techniques and applications have been achieved. Here, the latest studies of core materials for STOFETs are reviewed, mainly focusing on electrodes, dielectric layers and semiconductor layers. Then, the recent progress of some approaches for fabricating intrinsic STOFETs is mentioned, including solution methods, printing, and other methods. Detailed descriptions of the various stretchable electronic device applications of STOFETs are provided, along with their electrical/mechanical properties and examples of device applications. To conclude, a brief future outlook is presented.